Islam in Germany - Foreign attributions and identities Islam in Deutschland - Fremd-zuschreibungen und Identitäten - Nowar, Nina (Geographische Rundschau, 2022)
In the current public debate about Islam in Germany, vague anxieties and feelings of mistrust towards Muslims remain constant. External negative ascriptions and stereotypes of Islam overemphasise the religious identity of Muslims, regardless of whether they are religious or not. This forces them to position themselves between inadequate binary categories such as: "Are you muslim or German?" "Do you belong to us or to them?" This undifferentiated either-or debate contrasts with the self-perception of Muslims in Germany and leads to tensions with their own identification and the negative experience of non-belonging and exclusion. This article sheds light on the problems of those ascriptions for Muslims and uncovers examples of how Muslims set an antithesis through their continued civil society engagement.
CRIS-Team Scopus Importer:2024-12-16